2019
DOI: 10.1002/da.22949
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, circadian rhythm, and physical activity patterns in depressive and anxiety disorders: A 2‐week ambulatory assessment study

Abstract: Background Actigraphy may provide a more valid assessment of sleep, circadian rhythm (CR), and physical activity (PA) than self‐reported questionnaires, but has not been used widely to study the association with depression/anxiety and their clinical characteristics. Methods Fourteen‐day actigraphy data of 359 participants with current (n = 93), remitted (n = 176), or no (n = 90) composite international diagnostic interview depression/anxiety diagnoses were obtained from the Netherlands Study of Depression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
136
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(179 citation statements)
references
References 56 publications
(83 reference statements)
16
136
6
2
Order By: Relevance
“…The interviews were conducted by trained clinical research staff. The 384 participants included in this study were divided into three groups based on their CIDI diagnosis, analogous to Difrancesco et al (2019): (1) a current group with a depressive and/or anxiety disorder in the past 6 months at the 9-year follow-up interview (n = 100), (2) a remitted group with a lifetime depressive disorder and/or anxiety disorder but not in the 6 months prior to the 9-year follow-up interview (n = 190), and (3) a control group with no lifetime history of depressive and/or anxiety disorders (n = 94).…”
Section: Psychological Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…The interviews were conducted by trained clinical research staff. The 384 participants included in this study were divided into three groups based on their CIDI diagnosis, analogous to Difrancesco et al (2019): (1) a current group with a depressive and/or anxiety disorder in the past 6 months at the 9-year follow-up interview (n = 100), (2) a remitted group with a lifetime depressive disorder and/or anxiety disorder but not in the 6 months prior to the 9-year follow-up interview (n = 190), and (3) a control group with no lifetime history of depressive and/or anxiety disorders (n = 94).…”
Section: Psychological Medicinementioning
confidence: 99%
“…Severity of depressive and anxiety symptoms were assessed with the 30-item Inventory of Depressive Symptomatology (IDS; Rush, Gullion, Basco, Jarrett, and Trivedi, 1996) and the Beck Anxiety Inventory (BAI; Beck, Epstein, Brown, and Steer, 1988). Analogous to Difrancesco et al (2019), the number of comorbid psychiatric disorders was the sum of current depressive and anxiety diagnoses at 9-year follow-up. Frequency of depressive or anxiety disorders was calculated as a count of the number of waves at which patients reported a depression and/or anxiety diagnosis during the in-between follow-up periods (ranging from 1-5 waves).…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…For anxiety, relatively common at older age, it was shown that more fragmented 24-h activity rhythms were associated with higher odds of having an anxiety disorder [52], and that lower activity levels and a lower mesor were associated with current anxiety [48]. Additionally, disrupted 24-h activity rhythms have also been linked to more suicidal behaviors [63,64], but the causality of this association remains to be determined.…”
Section: Other Psychiatric Disorders In Late Lifementioning
confidence: 99%
“…The aim of this study was to explore perceived burden and adherence to smartphone-based EMA questionnaires in persons with affective disorders sampled from the Ecological Momentary Assessment (EMA) and Actigraphy sub-study (NESDA-EMAA) [19,20]. As well as persons with affective disorders, the cohort also included remitted persons and healthy controls.…”
Section: Introductionmentioning
confidence: 99%